A Portable Vortex Mixer With Object Detection Sensors Using TFT ILI9341 Control Display - Hidayati, Rinda Nur; Gunawan, Indra; Hendryani, Atika; Lestari, Gita Rindang; Salsabila, Natasya H (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2024)
A vortex mixer can be utilized for repetitive sample-mixing tasks that need execution over a predetermined period. The subject of this study is a device known as a vortex mixer, which is used to rapidly homogenize liquids in a compact container. The module's design aims to produce a portable vortex mixer with an object detector for use in the solution-mixing process. The module comprises a circuit controlled by ESP32, an infrared sensor for object detection, and a TFT LCD ILI9341 for display. A charging battery can also charge this device, making it easier to transport. This instrument has three degrees of speed: the low-level ranges from 300 to 500 RPM, the medium level ranges from 600 to 1500 RPM, and the high level extends from 1600 to 2500 RPM. The results reveal that the motor speed accuracy of the vortex mixers is low at 95.78%, medium at 97.49%, and high at 99.19%. Moreover, the battery life is lengthy, with an average charging time of 2.62 hours and a discharging time of 9.7 hours for 300 RPM; 7.34 hours for 600 RPM; and 3.03 hours for 1600 RPM, respectively.